Bildungsroman in Charles Dickens’s Great Expectations and James Joyce’s A Portrait of the Artist as a Young Man - Lata, Afrin Sultana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.